Evaluation of Xanthone and Cinnamoylbenzene as Anticancer Agents for Breast Cancer Cell Lines through In Vitro and In Silico Assays - Yehezkiel Steven Kurniawan; Hanif Amrulloh; Ervan Yudha; Nela Fatmasari; Faris Hermawan; Anggit Fitria; Harno Dwi Pranowo; Eti Nurwening Sholikhah; Jumina Jumina (Pandawa Institute, 2025)
Breast cancer is a severe global disease for women as the number of deaths increases annually. Therefore, attempts to find new anticancer agents are critical and inevitable. In this work, we report the investigation on the anticancer activity of xanthone and cinnamoylbenzene compounds against two breast cancer cell lines, i.e., T47D and MCF-7, through experimental in vitro and theoretical in silico assays. Xanthone and cinnamoylbenzene exhibit anticancer activity with a half-maximal inhibitory concentration (IC50) of 136.7–194.3 and 235.8–262.4 µg/mL against T47D and MCF-7 cancer cells, respectively. Cinnamoylbenzene generates less cytotoxicity to normal Vero cells with a selectivity index of 1.095–2.102. The molecular docking studies agree with the experimental data in which cinnamoylbenzene is more active against T47D with an IC50 of 136.7 µg/mL due to Topoisomerase II inhibition through π-π stacked interactions with Adenine12 and Guanine13 nitrogen bases. Meanwhile, xanthone is more active against MCF-7 with an IC50 of 235.8 µg/mL due to EGFR inhibition through van der Waals interaction and hydrogen bond with Glutamic acid767 and Methionine769 amino acid residues, respectively. Additionally, the pharmacokinetic parameters of xanthone and cinnamoylbenzene are predicted through absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis, and they show better suitability than doxorubicin as the commercial anticancer drug.